Kesulitan Belajar Pasca Pendemi COVID-19 di MTs Al-Amiriyah Blokagung Banyuwangi - Anyes Lathifatul Insaniyah; Rista Angraeni (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2022)
Learning difficulties are one of the learning problems. Learning difficulties experienced by students of MTs Al-Amiriyah Blokagung after the COVID-19 pandemic were due to limited time and place to study because students could not study at school as they should. In this study, it is limited by learning difficulties in learning Arabic which is a foreign language or second language for students who need a lot of practice. The purpose of this study was to find out what factors influence the difficulty of learning Arabic and to find out the teacher's efforts in overcoming difficulties in learning Arabic. The research method used is descriptive qualitative. The results of the study indicate that there are two factors that influence the difficulty of learning Arabic, namely internal factors due to laziness and lack of interest in student learning. And external factors caused by the learning environment. The teacher's efforts in overcoming the difficulties of learning Arabic are by creating study groups to foster student interest and provide motivation to learn during the COVID-19 pandemic.